The Attitudes towards Death of Undergraduate Students in the Faculty of Education, Nakhon Ratchasima Rajabhat University - Somkarn, Aekaphon; Akkhachat, Manit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This study aimed 1) to study the attitudes towards death and 2) to compare the attitudes towards death classified by gender of undergraduate students in the faculty of education, Nakhon Ratchasima Rajabhat University. The samples of this study consisted of 195 third year undergraduate students, selected from 17 programs in the Faculty of Education, Nakhon Ratchasima Rajabhat University in Academic year 2560. Research instrument was the attitude questionnaire, which the content has been validated by three experts in the field. The reliability was 0.93. The statistics for data analysis were Percentage, Mean, Standard Deviation, and Inferential statistics such as T-Test. The results showed that : 1. the attitudes towards death of undergraduate students in the faculty of Education, Nakhon Ratchasima Rajabhat University in the overall picture were at the fair level (x̅ = 3.43, S.D. = 0.58). 2. The comparison of the attitudes towards death of undergraduate student in the Faculty of Education, Nakhon Ratchasima Rajabhat University classified by gender revealed that students with different gender had no statistically significant differences in the overall picture. It was also found that the attitudes towards death of students with different gender were not different at the statistically significant difference of .05 in all aspects.